An Auto Ethnographic Study on Communicative Approach in Teaching English Syntax in a University Context - Abdullah Abdullah; Nurdin Noni; Muhammad Basri; Agussalim Djirong (Universitas Negeri Makassar, 2023)
This research employed an auto ethnographic study. It is a method used to describe the journey of the researcher in teaching English Syntax for three years in academic years 2015 to 2017. The problem in this research is how the lecturer implemented the communicative approach in teaching English Syntax in an Indonesian Higher Education Context. The Method used in this research is qualitative method. The subject of this research was the students and the lecturer of English department, Faculty of Language and Literature, Makassar State University. The instrument of the research was interview and auto ethnography reflection (lecturer personal reflection). Technique of the data collection used individual in-depth interview. The result of the data analysis indicated that the implementation of the communicative approach in teaching English Syntax run well because the students felt satisfy to join the class, from the class start until the end. The implementation was divided into three steps. The first is preparation; the lecturer has already prepared the teaching material well, the learning objective, and teaching method and strategy. The second is implementation the communicative approach in teaching English Syntax, and the third is evaluation. The all of the steps are run well in teaching English Syntax through the communicative approach. It can be concluded that teaching English Syntax through communicative approach was very good and successful, and get a good impact for the students in improving their language knowledge and skills. Keywords: an auto ethnographic study, Syntax, and communicative approach